Logistic Сompanies and their Influence on World Politics - A. S. Burnasov (MGIMO University Press, 2013)
In article the history and the modern factors providing success of the logistic companies is considered. Questions of their participation in modern system of the international relations and world politics are especially considered. The main tendencies which have created the international logistic companies are given, key factors of their influence on participants of the international relations are studied. The assessment is given to interaction of the state and the logistic companies